Desempenho, metabolismo e microbiota intestinal de leitões alimentados com rações contendo probióticos e simbióticos - Possamai, Maikel (2010)
Two experiments were conducted to evaluate the effect of using probiotics and symbiotic in piglets diets in the nursery phase. The first experiment was the performance of piglets from 21 to 35, from 36 to 49 days and in total period, being also held the count of lactic bacteria, fecal coliforms and clostridia in the piglets faeces at 35 and 49 days old. The economic viability of probiotics and symbiotic used in piglets diets was also evaluated. There were used 120 piglets, with 21 days old, with initial average weight of 5.80 ± 0.30 kg, distributed in a randomized blocks design, in a factorial scheme consisting of two levels of probiotics (0.30 and 0.60%) and three levels of inulin inclusion (0.00; 0.25 and 0.50%), totalizing six treatments with five replicates. In the metabolism trial were used 24 barrows, with average initial weight of 18.00 ± 0.38 kg, distributed individualy in metabolic cages, and the experimental design and treatments used were the same described in the performance experiment, with four replicates. In this trial were determined the values of digestible energy, metabolizable energy, the digestibility and metabolizability coefficients of gross energy and at the end of metabolism trial, were collected fecal samples, by means of retal massage to determine fecal pH. The inclusion of probiotic and inulin in the diets did not influence (P>0.05) the performance of piglets, from 21 to 35 and from 21 to 49 days of age, the cost index, the index of economic efficiency, the count of lactic bacteria, fecal coliforms and clostridia in the faeces. In the metabolism trial was observed that the inclusion of probiotics in the diets did not influence in the energy metabolization. Nevertheless, the levels of inclusion of inulin reduced (P<0.05) the digestible energy and the digestibility coefficient of gross energy, but did not influence in the coefficient of gross energy metabolization. The pH fecal values were not influenced by the inclusion of probiotic and symbiotic. The use of probiotic and inulin, and their association, did not change the performance, thefaeces microbial counts, the economic viability and gross energy metabolization of piglets from 21 to 49 days old